Edukasi Gizi dan Pemantauan Pertumbuhan Balita Bagi Kader sebagai Upaya Pencegahan Stunting di Posyandu Delima Padukuhan Miri, Pendowoharjo, Bantul (Lembaga Pengembangan Kinerja Dosen, 2026)
Stunting remains a chronic nutrition problem that requires strengthening community-based interventions, particularly through optimizing the role of posyandu cadres. This article aims to describe nutrition education and child growth monitoring for cadres as a strategy to prevent stunting at Posyandu Delima. The method employed was a participatory community empowerment approach based on health education. The activities were conducted through several stages, including needs assessment, development and delivery of nutrition education, hands-on practice in child growth monitoring, cadre mentoring, and evaluation with reflective feedback. The results showed an improvement in cadres’ knowledge and skills in interpreting growth indicators, identifying early risks of nutritional problems, and delivering structured nutrition education to caregivers of under-five children. Strengthening cadre capacity contributed to better quality of child growth monitoring and reinforced the role of posyandu as a community-based primary health service. In conclusion, integrated nutrition education and child growth monitoring are effective in supporting stunting prevention efforts and are aligned with national policies on strengthening maternal and child health services.